2018
DOI: 10.1080/10522158.2018.1499063
|View full text |Cite
|
Sign up to set email alerts
|

Transition to parenthood: it does not get easier the next time. Exploring ways to support well-being among parents with newborns

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
14
1
Order By: Relevance
“…First, this is a period characterized by great expression of needs and requests for support, particularly by women (Levy-Shiff, 1999;Cowan and Cowan, 2000); thus, the unique effects of stress communication underlying the activation of DC behaviors should be better understood. This is especially relevant given the fact that interpersonal relationship skills (e.g., skills to communicate effectively and to ask for help in time of need) may contribute more for couples' adjustment to the birth of a child than their social network (Ketner et al, 2018). Second, several stressors of this period are likely to be appraised as concerning both members of the couple (i.e., transition to parenthood as a "we stress" period).…”
Section: Introductionmentioning
confidence: 99%
“…First, this is a period characterized by great expression of needs and requests for support, particularly by women (Levy-Shiff, 1999;Cowan and Cowan, 2000); thus, the unique effects of stress communication underlying the activation of DC behaviors should be better understood. This is especially relevant given the fact that interpersonal relationship skills (e.g., skills to communicate effectively and to ask for help in time of need) may contribute more for couples' adjustment to the birth of a child than their social network (Ketner et al, 2018). Second, several stressors of this period are likely to be appraised as concerning both members of the couple (i.e., transition to parenthood as a "we stress" period).…”
Section: Introductionmentioning
confidence: 99%
“…The many biological, social and psychological changes during the transition to parenthood and the postpartum period can trigger parental mental health problems [ 11 ]. For example, hormonal changes [ 12 ], sleep issues [ 13 ], psychosocial stress [ 14 ], and the adaption to parenthood [ 15 ] are known for their potential to trigger symptoms of anxiety and depression in parents during the postpartum period (for a detailed review, see [ 16 , 17 ]). The first months postpartum are also a critical period for key developmental processes for the infant [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [ 11 ] investigated the factors predicting two types of parents’ wellbeing: individual wellbeing and parenting-related wellbeing. They found that non-first-time parents were not better off than first-time parents regarding wellbeing and marital relationship quality.…”
Section: Introductionmentioning
confidence: 99%